Digestive n‐6 Lipid Oxidation, a Key Trigger of Vascular Dysfunction and Atherosclerosis in the Western Diet: Protective Effects of Apple Polyphenols - Bolea, Gaëtan; Philouze, Clothilde; Dubois, Mathilde; Risdon, Sydney; Humberclaude, Anaïs; Ginies, Christian; Charles, Anne‐Laure; Geny, Bernard; Reboul, Cyril; Arnaud, Claire; Dufour, Claire; Meyer, Grégory (Molecular nutrition & food research, 2021)
Scope A main risk factor of atherosclerosis is a Western diet (WD) rich in n‐6 polyunsaturated fatty acids (PUFAs) sensitive to oxidation. Their oxidation can be initiated by heme iron of red meat leading to the formation of 4‐hydroxy‐2‐nonenal (4‐HNE), a cytotoxic aldehyde. An increased 4‐HNE production is implicated in endothelial dysfunction and atherosclerosis. By contrast, a diet rich in proanthocyanidins reduces oxidative stress and arterial diseases. This study evaluates the effects of a WD on vascular integrity in ApolipoproteinE (ApoE−/−) mice and the protective capacity of apple extract and puree rich in antioxidant proanthocyanidins. Methods and results ApoE‐/‐ mice are fed during 12 weeks with a WD with or without n‐6 PUFAs. Moreover, two WD + n‐6 PUFAs groups are supplemented with apple puree or phenolic extract. An increase in digestive 4‐HNE production associated with a rise in plasmatic 4‐HNE and oxidized LDL concentrations is reported. Oxidizable n‐6 PUFAs consumption is associated with a worsened endothelial dysfunction and atherosclerosis. Interestingly, supplementations with apple polyphenol extract or puree prevented these impairments while reducing oxidative stress. Conclusion n‐6 lipid oxidation during digestion may be a key factor of vascular impairments. Nevertheless, an antioxidant strategy can limit 4‐HNE formation during digestion and thus durably protect vascular function. A Western diet rich in n‐6 polyunsaturated fatty acids was responsible for a higher lipid oxidation resulting in increased digestive and plasmatic concentrations of 4‐hydroxy‐2‐nonenal concentrations in Apolipoprotein‐/‐ mice. A subsequent impairment of vascular function and an increase in atherosclerosis development were observed. A polyphenol supplementation (apple) was further demonstrated to inhibit lipid oxidation during digestion and prevent vascular impairments.